Sharia Compliance, Islamic Corporate Governance dan Non Performing Financing Terhadap Pengungkapan Fraud Bank Umum Syariah - Mifthahul Ridha; Umiyati Umiyati (Jurnal Akuntansi dan Governance, 2022)
This study aims to analyze the effect of sharia compliance, Islamic corporate governance, and non-performing financing on the disclosure of fraud in Islamic commercial banks in Indonesia. With quantitative approach this study analyzes data population in the form of Islamic Commercial Banks in Indonesia using purposive sampling method. Data were obtained from the annual financial statements and GCG reports during 2017-2020 and were analyzed using the panel data regression method. The results of this study indicate that the Islamic Income Ratio (IsIR) and Profit-Sharing Ratio (PSR) have significant effects on the disclosure of fraud in Islamic Commercial Banks. While Zakat Performing Ratio (ZPR), Islamic Corporate Governance, and Non-Performing Financing (NPF) do not significantly affect the disclosure of fraud in Islamic Commercial Banks.